Good Samaritan Law: A Look at the Necessity of its Implementation in Malaysia: (Good Samaritan Law: Satu Tinjauan Keperluan Kewujudannya di Malaysia) (Kanun: Jurnal Undang-undang Malaysia, 2019)
Generally, there is no liability or legal implication that is applied if one does not help another individual in trouble. However, on humanitarian grounds, several countries have implemented a 'good Samaritan law' which is meant to prevent people from refusing to come forward to help an individual who has been hurt or injured for fear of legal action due to unintentional injury or wrongful death. Although there exist numerous difficulties, especially in courts in determining the application of the concepts of good intention, the level of emergency and reasonable action or decision, the implementation of such a law encourages the 'good Samaritan' culture. In implementing this, the court's detailed study and discretion is very much required so that the party that receives the help does not suffer increased "pain, damage or injury" when the "good Samaritan" is protected from legal liability. Therefore, the aim of this article is to study the necessity of the implementation of a "good Samaritan law" in Malaysia by looking at the experiences of the United States and Australia. This article is based on a qualitative study employing the library research methodology.Keywords: Good Samaritan, civil liability, emergency, good faith, legal implications